2016
DOI: 10.1002/cjoc.201600365
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Commercial Chinese Cereal and European Grape Vinegars Using 1H NMR Spectroscopy Combined with Multivariate Analysis

Abstract: A holistic and comparative quality assessment of vinegars from different countries is needed with international trade of vinegar become frequent. In this study, compounds characterization and comparison of commercial-grade Chinese cereal and European grape vinegars were performed using 1 H NMR spectroscopy coupled with principal component analysis (PCA) and orthogonal projection to latent structures discriminate analysis (OPLS-DA). The results showed that Balsamic vinegars of Modena were clearly discriminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…A representative 1 H NMR spectrum is presented in Figure 3 for the balsamic vinegar with honey. The assignment of the NMR peaks enabled the identification of 27 metabolites, including mono and oligosaccharides, amino acids as well as other organic acids (acetic, citric, formic, lactic, malic and succinic acids) and phenolic compounds (gallic acid, catechin, epicatechin, chlorogenic acid, caffeic acid and p-coumaric acid), in agreement with previous NMR studies [ 10 , 11 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A representative 1 H NMR spectrum is presented in Figure 3 for the balsamic vinegar with honey. The assignment of the NMR peaks enabled the identification of 27 metabolites, including mono and oligosaccharides, amino acids as well as other organic acids (acetic, citric, formic, lactic, malic and succinic acids) and phenolic compounds (gallic acid, catechin, epicatechin, chlorogenic acid, caffeic acid and p-coumaric acid), in agreement with previous NMR studies [ 10 , 11 ].…”
Section: Resultssupporting
confidence: 87%
“…In this sense, UV-Vis and infrared absorption spectroscopy techniques can be employed to assess the antioxidant and antimicrobial potential of vinegars as well as to identify bioactive compounds (organic acids, polyphenols, flavonoids and others) that discriminate vinegars from diverse origins [ 6 , 7 , 8 , 9 ]. Moreover, 1 Η-NMR has been utilized for the differentiation of various types of cereal and grape vinegars in relation to their metabolic profiles [ 10 , 11 , 12 ], as well as GC-MS and GC-FID were used to assess the volatile profile of vinegars and determine metabolites evident of natural vinegars [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The LBP content in WFV was 8.94 ± 0.27 mg/mL, and the betaine and carotenoid levels in WFV were 2.88 ± 0.22 and 0.42 ± 0.02 mg/mL, respectively. Wang et al [ 27 ] found that the betaine content (>0.59 mg/mL) in Chinese cereal vinegar was higher than that in European grape vinegar, which was less than the betaine content in WFV. Ali et al [ 28 ] found that the carotenoid contents in red and blackened jujube vinegar were 0.45–1.00 and 1.48–3.47 mg/100 mL, which was much lower than the vinegar we produced.…”
Section: Resultsmentioning
confidence: 99%
“…The polysaccharide content was significantly decreased to 7.26 ± 0.26 mg/mL in WFW, and then significantly rose to 8.94 ± 0.27 mg/mL in WFV (p < 0.05). Additionally, the betaine contents (2.68-2.94 mg/mL) showed no significant difference during the fermentation processes (p > 0.05), and betaine can adjust the taste and flavor of fruit vinegars [27]. The carotenoid content decreased from 0.58 ± 0.08 mg/mL to 0.42 ± 0.02 mg/mL along throughout the entire fermentation processes, which was mainly due to the oxidation reaction and degradation in the fermentation stages [28].…”
Section: Bioactive Components Of Wolfberry Fruit Vinegar During Ferme...mentioning
confidence: 91%